USGS “Did You Feel It?”—Science and Lessons From 20 Years of Citizen Science-Based Macroseismology - Quitoriano, Vincent; Wald, David J. (Frontiers in Earth Science, 2020)
The U.S. Geological Survey (USGS) “Did You Feel It?” (DYFI) system is an automatic method for rapidly collecting macroseismic intensity (MI) data from internet users’ shaking and damage reports and for generating intensity maps immediately following felt earthquakes. DYFI has been in operation for nearly two decades (1999–2019) in the United States, and for nearly 15 years globally. During that period, the amount of data collected is astounding: Over 5 million individual DYFI intensity reports—spanning all magnitude and distance ranges—have been amassed and archived. DYFI allows for macroseismic data collection at rates and quantities never before imagined, and thus high-quality MI maps can be made almost immediately, and with more complete coverage at higher resolution than in the past. DYFI also allows for valuable positive interactions of the citizenry with a Federal science agency. In essence, the widespread adoption of DYFI – along with ShakeMap—has facilitated the general acceptance of the very concept of shaking intensity, fundamentally improving our agency’s ability to communicate both hazard and risk to the population. DYFI effectively confirms the importance of reporting and inculcating the public’s understanding of intensity – in addition to magnitude – for a proper perspective of earthquake risk-related decision-making. Furthermore, the vast amount of DYFI data allows for data-rich analyses of otherwise intractable seismological, sociological, and earthquake impact studies, such as quantifying the shaking due to induced earthquakes, human response and risk perception, relating recorded shaking metrics to macroseismic effects, and the attenuation of intensity with magnitude and distance. Naturally, web-based data collection also poses challenges. After two decades of experience acquiring data with the DYFI system, we address some of these challenges by documenting refinements to our algorithmic and operational procedures that have evolved over that time. Lastly, we outline new opportune research and development directions for our DYFI approach to citizen seismology.